PENULISAN NAMA DIRI DAN NAMA JENIS DALAM PRODUK HUKUM INDONESIA - H.M., Junaiyah (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
In the various Indonesian language texts, the writing of proper name andspecies are often incorrect. This article provides guidance on how to writethe proper name and species properly according to Indonesian SpellingEnhanced. The debates between linguists and experts in law are oftenstopped when the names are nomenclature in the law experts’ opinion. Yet,the meaning of nomenclature is “a special term used in a certain discipline”, and not proper name. Proper name is written with a capital letter, butnomenclature and species are written with an initial small letter.